Redox proteomics reveal a role for peroxiredoxinylation in stress protection - Gerhard Seisenbacher; Zrinka Raguz Nakic; Eva Borràs; Eduard Sabidó; Uwe Sauer; Eulalia de Nadal; Francesc Posas (Cell Reports)
Summary: The redox state of proteins is essential for their function and guarantees cell fitness. Peroxiredoxins protect cells against oxidative stress, maintain redox homeostasis, act as chaperones, and transmit hydrogen peroxide signals to redox regulators. Despite the profound structural and functional knowledge of peroxiredoxins action, information on how the different functions are concerted is still scarce. Using global proteomic analyses, we show here that the yeast peroxiredoxin Tsa1 interacts with many proteins of essential biological processes, including protein turnover and carbohydrate metabolism. Several of these interactions are of a covalent nature, and we show that failure of peroxiredoxinylation of Gnd1 affects its phosphogluconate dehydrogenase activity and impairs recovery upon stress. Thioredoxins directly remove TSA1-formed mixed disulfide intermediates, thus expanding the role of the thioredoxin-peroxiredoxin redox cycle pair to buffer the redox state of proteins.